Nutritional characterization of acorn flour (a traditional component of the Mediterranean gastronomical folklore) - Silva, Sara (2017)
Abstract Nowadays, acorns, the fruits of Quercus trees, are mostly associated with animal feed. However they are part of the traditional gastronomical folklore of severalMediterranean countries. Though several uses can be mentioned, one of the most common uses is powdering the acorns in order to produce a flour that can substitute regular corn flour in the manufacture breads and cakes. An example of this is acorn bread, a typical Portuguese loaf.However, to the best of our knowledge, there is no information about the nutritional value of these flours. As such, the main goal of this work was to describe the nutritional value of acorn flours from two different subspecies of Quercus abundant in Portugal (Quercus ilex and Quercus rotundifolia) obtained using two different traditional methods (drying and roasting). The results demonstrated that all flours possessed interesting nutritional properties, namely the absence of gluten and elevated values of both monounsaturated and polyunsaturated fatty acids. Because of these facts and it’s low production cost, acorn flour poses as an interesting alternative to traditional flours particularly for gluten intolerant individuals.